UPAYA MENINGKATKAN HASIL BELAJAR LOMPAT JAUH GAYA JONGKOK MELALUI PERMAINAN TRADISIONAL PADA SISWA KELAS VI A SD AGUNG PERSADA BANDAR KHALIPAH KABUPATEN DELI SERDANG T.A. 2017/2018 - Rahmat Cahyadi (Universitas Islam Negeri Sumatera Utara Medan, 2018)
The purpose of this study was to improve the learning outcomes of the squat-style long jump through traditional games in grade VI A SD Agung Persada Bandar Khalipah, Deli Serdang Regency T.A. 2017/2018. The research method used in this research is classroom action research. The location of this research is SD Agung Persada Bandar Khalipah, Deli Serdang Regency, T.A. 2017/2018. The subjects receiving the action in this study were all students of class VI A SD Agung Persada Bandar Khalipah, Deli Serdang Regency, T.A. 2017/2018. According to the results, it can be said that learning using traditional games can improve the long jump learning outcomes of the squat style in class VI A SD Agung Persada Bandar Khalipah, Deli Serdang Regency T.A. 2017/2018.